2007
DOI: 10.1164/rccm.200610-1473oc
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Social Environment in Children and Adolescents with Asthma

Abstract: Rationale: Biopsychosocial models of asthma have been proposed in the literature, but few empirical tests of social factors at various levels of influence have been conducted. Objectives: To test associations of neighborhood, peer, and family factors with asthma outcomes in youth, and to determine the pathways through which these social factors operate. Methods: Observational study of youths with asthma (n 5 78). Measurements and Main Results: Youths completed questionnaires about neighborhood problems, peer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 27 publications
4
92
0
9
Order By: Relevance
“…In adulthood, SED is assessed based on factors in an individual's own background such as income, occupation, and education level, whereas in childhood, SED is typically assessed based on these factors for the parents. SED is a widely recognized concern because long-lasting adverse effects on health have been robustly and consistently reported throughout the lifespan (Chen et al 2007;Chen et al 2002;Cohen et al 2010;Evans and Kim 2010;Seeman et al 2010) . With respect to psychological health development, exposure to SED has been associated with poor language, cognitive deficits, and behavioral problems during childhood (Blair and Raver 2012;Brooks-Gunn and Duncan 1997;Evans 2004;McLoyd 1998).…”
Section: Socioeconomic Disadvantages and Health Across The Lifespanmentioning
confidence: 99%
“…In adulthood, SED is assessed based on factors in an individual's own background such as income, occupation, and education level, whereas in childhood, SED is typically assessed based on these factors for the parents. SED is a widely recognized concern because long-lasting adverse effects on health have been robustly and consistently reported throughout the lifespan (Chen et al 2007;Chen et al 2002;Cohen et al 2010;Evans and Kim 2010;Seeman et al 2010) . With respect to psychological health development, exposure to SED has been associated with poor language, cognitive deficits, and behavioral problems during childhood (Blair and Raver 2012;Brooks-Gunn and Duncan 1997;Evans 2004;McLoyd 1998).…”
Section: Socioeconomic Disadvantages and Health Across The Lifespanmentioning
confidence: 99%
“…Apart from this, the social environment is an important determinant of health [35]. Social support influences human beliefs and attitudes towards their health [36].…”
Section: Societal Perspective: Role Of Peersmentioning
confidence: 99%
“…Recently, Chen and colleagues investigated the mechanism by which neighborhood and family level social and psychological factors influence asthma [77]. They found that lower levels of family support affected asthma symptoms and pulmonary function through biological pathways, such as allergic inflammation, whereas community factors influenced asthma symptoms through behavioral pathways, such as higher smoking rates.…”
Section: Social and Psychosocial Risk Factors For Asthmamentioning
confidence: 99%